The role of the 4C model (critical thinking, communication, collaboration, creativity) in developing students’ language skills - Ochilova, Vazira (The Lingua Spectrum, 2025)
This article analyzes the role and significance of the 4C model (Critical thinking, Communication, Collaboration, Creativity) in developing students ’ language skills. In the process of language learning, attention is paid not only to the acquisition of linguistic knowledge, but also to the development of modern competencies, such as critical thinking, communication, cooperation and creativity. Within the framework of the study, a pedagogical experiment was carried out among students of a higher educational institution, studying the effectiveness of educational activities organized on the basis of the 4C model in the development of language skills. The results obtained showed that English classes organized on the basis of the 4C model are more effective than traditional methods in developing students ’ listening, speaking, reading and writing skills. The article also analyzes the basic principles and methods of applying the 4C model to the language teaching process, the difficulties that may arise in this process, and their solutions. Based on the results of the study, scientific and practical recommendations have been developed to apply the 4C model to the language teaching process in higher education institutions. Keywords: 4C model, language skills, critical thinking, communication, collaboration, creativity, language teaching methodology.